Five-year survivors from brain metastases treated with stereotactic radiosurgery: Biology, improving treatments, or just plain luck?. Issue 2 (13th December 2022) - Pearce, Jane B; Hsu, Fang-Chi; Lanier, Claire M; Cramer, Christina K; Ruiz, Jimmy; Lo, Hui-Wen; Xing, Fei; Smith, Margaret; Li, Wencheng; Whitlow, Christopher; White, Jaclyn J; Tatter, Stephen B; et al.
Abstract: Background: Improvements in therapies have led to an increasing number of long-term survivors of brain metastases. The present series compares a population of 5-year survivors of brain metastases to a generalized brain metastases population to assess for factors attributable to long-term survival. Methods: A single institution retrospective review was performed to identify 5-year survivors of brain metastases who received stereotactic radiosurgery (SRS). A historical control population of 737 patients with brain metastases was used to assess similarities and differences between the long-term survivor population and the general population treated with SRS. Results: A total of 98 patients with brain metastases were found to have survived over 60 months. No differences between long-term survivors and controls were identified with regards to the age at first SRS ( P  = .19), primary cancer distribution ( P  = .80), and the number of metastases at first SRS ( P  = .90). Cumulative incidence of neurologic death at 6, 8 and 10 years for the long-term survivor cohort was 4.8%, 16%, and 16% respectively. In the historical controls, cumulative incidence of neurologic death reached a plateau at 40% after 4.9 years. A significant difference in the distribution of burden of disease at the time of the first SRS was found between the 5-year survivors and the control ( P  = .0049). 58% of 5-year survivors showed no evidence of clinical disease at the last follow-up. Conclusion: Five-year survivors of brain metastases represent a diverse histologic population, suggesting a small population of oligometastatic and indolent cancers exist for each cancer type.